An Analysis On Writing Task Of English Textbook Entitled Talk Active For The Tenth Grade Student Of Senior High School - Ambarwati, Yulia Marheni, Drs. Djoko Srijono, M.Hum, Dr. Dwi Haryanti, M.Hum (2014)
The aim of this research are to describe whether or not the writing tasks on English Textbook entitled Talk Active for the tenth grade students of Senior High School are compatible with the writing tasks as suggested by Raimes and to describe whether or not the writing task facilitate to the students achieve the competency. This research is a descriptive research. The methods of collecting data are (1) reading the English textbook entitled Talk Active and (2) classifying the tasks containing writing task. The data are the materials of writing tasks found in English textbook entitled Talk Active. Data source is English textbook entitled "Talk Active". The data were analyzed by steps: (1) finding the writing tasks in the textbook, (2) coding the data, (3) judging whether the writing tasks in the English textbook appropriate with the writing task as suggested by Raimes, and (4) drawing conclusion and giving suggestion. Based on the analyzed data, the writing tasks found in the textbook are conversion, sentence combining, filling in the blank without translation, question answer, summary writing, scrambled paragraph, cloze test, filling in the blank with translation, free composition and write the text based on the topic provided. The percentage for the writing tasks provided in Talk Active based on the percentage, referring to the schema of quality classification proposed by Arikunto (2010) is 71,43%. It means that the writing task is good in developing writing skill. Among the fourteen sub-categories in criteria of writing task suggested by Raimes there are ten sub-categories that are provided in the textbook, the second result is the writing task of the textbook facilitate the students to achieve the competency of writing skill.